Proximal iterated function systems using cyclic Meir-Keeler contractions and an application to fractal theory - Unni, A. Sreelakshmi; Pragadeeswarar, V. (Fixed point theory and algorithms for sciences and engineering, 2025)
In this paper, we develop the proximal iterated function systems ( P I F S ) using cyclic Meir-Keeler contractions and hence give an application in the fractal theory by constructing fractals using the new I F S . Furthermore, we extend the results to countable P I F S .